Counseling on processing and marketing strategies for agricultural, livestock and fishery products to increase household income - Ardiansyah, Muhammad; Asri, Haryanto; Indriani, Indriani; said, Sadly Ashari; Ht, A. Muh. Ayyub (Lebah, 2025)
The strategy for processing and marketing agricultural, livestock and fishery products is an important effort to increase household income, especially in rural communities. This outreach identifies various innovative processing methods, such as drying, canning, and value-added processing, that can improve product quality and marketability. In addition, effective marketing strategies, including direct marketing to consumers through digital platforms, product exhibitions, and cooperation with local stores, are also outlined. This community service activity aims to improve household income in Bonda Village, Mamuju Regency, West Sulawesi Province. This service is to provide education about methods of processing and marketing products from the agricultural, livestock and fisheries sectors to increase family income. In this service, the approach used includes surveys and case studies. The survey was carried out to collect basic information regarding the knowledge and processing and marketing practices carried out by farmers, livestock breeders and fishermen at the research location. Next, case studies are used to explore examples of successful implementation of efficient strategies in several communities. The findings from this service indicate that the application of appropriate processing methods and effective marketing techniques can increase product sales and household income. It is hoped that these results can provide guidance for business actors in maximizing the potential of local products and improving the economic welfare of the community